ANALISIS SENYAWA FLAVONOID DAUN LAMUN Enhalus acoroides DI PERAIRAN PANTAI DESA WAAI KABUPATEN MALUKU TENGAH - Icak Darling Rahakbauw; Theopilus Watuguly (BIOPENDIX, 2016)
Background: The coastal waters of Waai Village are the waters located in Kecamatan Kecamatan, Central Maluku District. The potential of coastal resources in this area is quite a lot of seagrass (Seagrass). Although quite a lot but because of the lack of information related to the existing seagrass so that until now the utilization of seagrass in the area has not been maximized. This study aims to determine the total flavonoid compounds contained in the seagrass of Enhalus acoroides. Method: This research was conducted at Basic Chemical Laboratory, Faculty of Mathematics and Natural Sciences (FMIPA) Pattimura University Ambon. The study was conducted from March 20-28, 2016, with sampling location in coastal waters of Waai Village, Central Maluku District. The method used refers to the Chang method by using AlCl3 reagent. Result: Based on total analysis of flavonoid compound using laboratory experimental method obtained the average flavonoid level contained in Enhalus acoroides seagrass leaves of 3.569%. Conclusion: Seaweed leaves Enhalus acoroides taken from coastal waters of Waai Village contain flavonoid compounds with an average value of 3.5697%.